Human Interface and the Management of Information. Designing Information Environments Symposium on Human Interface 2009, Held as Part of HCI International 2009, San Diego, CA, USA, July 19-24, 2009, Proceedings, Part I - Smith, Michael J.; Salvendy, Gavriel; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2009)
This two-volume set LNCS 5617 and 5618 constitutes the refereed proceedings of the Symposium on Human Interface 2009, held in San Diego, CA, USA in July 2007 in the framework of the 13th International Conference on Human-Computer Interaction, HCII 2009 with 16 other thematically similar conferences. The 175 revised papers presented in the two volumes were carefully reviewed and selected from numerous submissions. The papers accepted for presentation thoroughly cover the thematic area of human interface and the management of information. The 82 papers of this first volume address the following major topics: supporting work, collaboration and business; product design and development; interacting with information, documents and knowledge; novel devices, interfaces and interaction environments; user-centered design and user experience in information systems.
Supporting Work, Collaboration and Business -- Product Design and Development -- Interacting with Information, Documents and Knowledge -- Novel Devices, Interfaces and Interaction Environments -- User-Centered Design and User Experience in Information Systems.
Keywords: User interfaces (Computer systems).; Human-computer interaction; Electronic data processing -- Management; Electronic commerce; Computers, Special purpose; Database management; Data mining; User Interfaces and Human Computer Interaction; IT Operations; e-Commerce and e-Business.; Special Purpose and Application-Based Systems; Database Management; Data Mining and Knowledge Discovery